Akibat Hukum Perjanjian Melalui Elektronik Ditinjau dari Pasal 1866 Kitab Undang-Undang Hukum Perdata: Legal Consequences of Agreements Through Electronic Judging From Article 1866 of the Civil Code - Arif Muhammad Simamora; Fahmi Fahmi; Yenni Triana (DOKTRINA: JOURNAL OF LAW, 2022)
The absence of a law that specifically regulates personal data of agreement users via electronic means often causes legal problems, both regarding issues of authenticity, authenticity and proof. This writing focuses on legal issues, namely how the problems with the authenticity, authenticity and integrity of the agreement electronically and how the validity of an agreement made electronically. The research method that the author uses is normative qualitative using secondary data and reinforced by primary data or field data. The results of the study show that the authenticity, authenticity and integrity of the agreement electronically can be carried out using digital forensic tools. the use of information through electronic media concerning a person's personal data must be carried out with the consent of the person concerned. Agreements made electronically/digitally have the same evidentiary power as agreements made through manuals. Judges can use a system of evidence with developments towards open evidence. Evidence obtained from anywhere as long as the truth can be accepted as long as it does not conflict with public order, considering that in conducting transactions in the current digital era, we will often use online media.